Optimization of the micronutrients sufficiency of feeding women and children on exclusively breastfeeding by enriching of the woman diet - Vera M. Kodentsova; Dmitry V. Risnik; Stanislav V. Pavlovich; Olga B. Ladodo (IP Berlin A.V., 2021)
A significant part of pregnant and lactating women have a lack of several micronutrients at once (vitamin D, group B, iodine, iron, etc.). The secretion of vitamins A, E, D, C, B1, B2, B6, B12, iodine and selenium into breast milk decreases with their insufficient consumption and insufficient provision of the nursing mother. The content of folates, calcium, magnesium, phosphorus in breast milk is maintained even if they are insufficient in the mother, however, enriching the diet with them during breastfeeding, improving the status of the mother, prevents the depletion of reserves in her body. The iron and zinc content in breast milk is determined by the mothers status during pregnancy. The intake of vitamin-mineral supplements or food products enriched with micronutrients during the pregravid period, during pregnancy and lactation leads to an improvement in the provision of a woman and her child by increasing the content of vitamins, iodine and selenium in breast milk. The use of vitamin-mineral supplements is an effective way not only to eliminate multiple micronutrient deficiencies in the diet and improve the status of a lactating woman, but also to optimize the vitamin composition of breast milk and the provision of an exclusively breastfed baby.